NEED ANALYSIS FOR DESIGNING ESP COURSE FOR MEDICAL STUDENTS - Carnando, Gea (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
English impacts many sectors of life, including job of people. The massive spread of English has brought a high demand on teaching English for many specific jobs. However, the teaching of English did not fulfill the significant needs of those workers, because the English that has been taught was general English. One types of the job that needs to learn ESP is the medical workers or in this study, a Doctor. Many barriers can impede communication between a doctor and a patient. Therefore, this study was conducted to find the need analysis by gathering data from 40 medical students, a doctor, an ME teacher, and a foreign patient using questionnaire and interview. The result showed how importance to conduct a need analysis to design an ME course.